Evaluation of corrective actions of feedback from clinicians on Clinical Laboratory Services at Bamenda Regional Hospital Laboratory, Cameroon - Victor N. Fondoh; Charles N. Awasom; Rebecca Enow-Tanjong; Richard M. Fondoh; Patrick Njukeng; Judith Shang; Juliana Ndasi; Moses Samje; Claris N. Muluh; Thompson N. Kinge (AOSIS, 2020)
Background: Customers' satisfaction is imperative for success. Clinical laboratories continuously strive to attain very high levels of customer satisfaction to serve their clients and maintain accreditation. The concept of customer satisfaction has not yet been asserted in most clinical laboratories in Cameroon. Objectives: Our objectives were to assess the satisfaction of clinicians with the laboratory services at the Bamenda Regional Hospital Laboratory, identify important challenges, corrective actions implemented and changes in satisfaction. Methods: This retrospective study reviewed secondary data from clinician satisfaction survey records from March 2017 and November 2017. Challenges and implemented corrective actions were identified for assessed statements of dissatisfaction (dissatisfaction rates ≥ 20%) on the March 2017 survey. Satisfaction rates in March 2017 and November 2017 were compared. Results: High levels of dissatisfaction were observed for general satisfaction, waiting time, communication, duty consciousness, specimen collection and approach on the March 2017 survey. The main challenges identified were: lack of respect for the expected length of the waiting time, poor attitude, inadequate information, staff shortage and inadequate supervision. Statistically significant reductions in rates of dissatisfaction were observed for general satisfaction, waiting time, communication, response to emergencies, issuing of results, specimen collection, approach and duty consciousness. Conclusion: Waiting time is a major cause of clinician dissatisfaction with laboratory services. The identification of clinicians' challenges and the effective implementation of corrective actions contribute to improvements in clinician satisfaction.